Optimasi Desain Cetakan Plastik Injeksi Knob Volume Untuk Mesin Two-Shot Injection Molding Dengan Metode Design For Manufacturing (Dfm) - Ahmad Latif; Nurato Nurato (Journal of Innovative and Creativity, 2025)
The manufacturing sector plays a crucial role in driving Indonesia’s economic growth, particularly in facing the challenges of globalization and demands for production efficiency. One of the commonly used manufacturing processes is injection molding due to its ability to produce high-precision plastic products in large quantities. This study aims to design an injection mold for producing a two-color volume knob made from clear polycarbonate (pc) and black acrylonitrile butadiene styrene (abs), using a sumitomo demag se75du-ci two-shot injection molding machine. The product presents a high level of complexity due to the use of two different materials and the need for efficient production to minimize defects such as short shots, flash, and product weight inconsistency. To address this, the two-shot injection molding method is employed, enabling the molding of two materials in a single production cycle. The mold design process is carried out systematically using the design for manufacturing method. The mold is designed using siemens nx software and further optimized through material flow simulation using moldex3d moldflow to predict potential defects and improve the mold design. This research is expected to provide an effective mold design solution that enhances product quality, process efficiency, and reduces the rejection rate in two-color knob production. The results of this study are intended to serve as a reference for implementing multi-material mold technology in the plastic manufacturing industry, especially for components with complex designs and specific visual requirements.